Intravenous Glucose Bag Monitoring System - Ramesh Kannan R; Esakkiram E; Priyan; Samuel Pakianathan; Vignesh V (International Journal of Medical Toxicology and Legal Medicine, 2025)
The Intravenous Glucose Bag Monitoring System is a technologically advanced solution to improve patient safety and healthcare efficiency by providing real-time monitoring of glucose levels during IV therapy. Traditional methods of manually monitoring IV fluids are susceptible to errors, which can result in fluid depletion or over-infusion, particularly in fast-paced hospital environments. This system integrates weight and flow rate sensors to automatically track glucose bag liquid level, infusion rate, and remaining time. The weight sensors measure the fluid volume by calculating the weight of the IV bag, while flow rate sensors ensure that the infusion is proceeding at the correct speed. Data from these sensors is wirelessly transmitted to a central monitoring system, accessible via mobile devices or hospital interfaces, allowing healthcare providers to monitor patient treatments remotely. Additionally, the system features an alert mechanism that notifies medical staff when glucose levels fall below a critical threshold or when the infusion rate deviates from preset parameters. This technology reduces the likelihood of IV-related complications, minimizes manual observation, and ensures timely intervention, leading to better patient outcomes and more efficient resource management in healthcare settings. Moreover, this system can be integrated with electronic medical records (EMR), allowing for seamless documentation of IV therapy data. This integration ensures that all information about glucose administration is recorded accurately, enabling better patient management and analysis of treatment outcomes.